Retinal response to systemic inflammation differs between sexes and neurons - Rodríguez-Ramírez, Kristy T.; Norte-Muñoz, María; Lucas-Ruiz, Fernando; Gallego-Ortega, Alejandro; Calzaferri, Francesco; García-Bernal, David; Martínez, Carlos M.; Galindo-Romero, Caridad; de los Ríos, Cristóbal; Vidal-Sanz, Manuel; Agudo-Barriuso, Marta (Frontiers in Immunology, 2024)
Neurological dysfunction and neuroinflammation are common events in severe infections such as sepsis, for which there is no treatment. There is a sexual dimorphism in the response to systemic inflammation in both patients and animal models, but there are few comparative studies. Here we have investigated the retinal response to systemic inflammation induced by intraperitoneal administration of lipopolysaccharide (LPS) in male and female mice. In LPS-treated animals of both sexes, there was transient retinal dysfunction, loss of vision-forming but not non-vision forming retinal ganglion cells (RGCs), retinal swelling, microglial activation, cell infiltration, and increase in TNF and IL-1β. Compared to females, males showed higher vision-forming RGC death, slower functional recovery, and overexpression of lymphotoxin alpha in their retinas. P2X7R and TNFR1 antagonism, alone or in combination, rescued vision-forming RGCs while P2X7R antagonism also rescued retinal function. Our results highlight the need to analyse males and females in preclinical studies of inflammatory diseases affecting the central nervous system.